Three new species of Tephrochlamys Loew (Diptera: Heleomyzidae: Heteromyzinae) from Oriental China, with a key to the Oriental species - Zeng, Wei; Ma, Fangzhou; Yang, Ding (Zootaxa, 2024)
The genus Tephrochlamys Loew, 1862, is a small genus in Heteromyzinae of the family Heleomyzidae. Only four species of this genus are known from the Oriental Realm so far: T. fasciata Czerny, 1924, T. javanensis Frey, 1934, T. japonica Okadome, 1967 and T. rufiventris Meigen, 1830. Here, we describe three new species of Tephrochlamys from Oriental China: Tephrochlamys wuyishanensis sp. nov., Tephrochlamys variegata sp. nov. and Tephrochlamys pengi sp. nov. A key to the Oriental species of Tephrochlamys is presented.